2015
DOI: 10.1007/s11302-015-9452-9
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling during development and ageing

Abstract: Extracellular purines and pyrimidines play major roles during embryogenesis, organogenesis, postnatal development and ageing in vertebrates, including humans. Pluripotent stem cells can differentiate into three primary germ layers of the embryo but may also be involved in plasticity and repair of the adult brain. These cells express the molecular components necessary for purinergic signalling, and their developmental fates can be manipulated via this signalling pathway. Functional P1, P2Y and P2X receptor subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 351 publications
(264 reference statements)
1
50
0
2
Order By: Relevance
“…). In contrast with this up‐regulation of A 2A receptors, other authors have shown that adenosinergic activities were unaffected by ageing in the cerebellum and substantia nigra (for a review see Burnstock & Dale, ). Additionally, a reduction in P2X receptor expression in ageing mouse brain has been described as their role in glial synaptic current generation (Lalo et al .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…). In contrast with this up‐regulation of A 2A receptors, other authors have shown that adenosinergic activities were unaffected by ageing in the cerebellum and substantia nigra (for a review see Burnstock & Dale, ). Additionally, a reduction in P2X receptor expression in ageing mouse brain has been described as their role in glial synaptic current generation (Lalo et al .…”
Section: Discussionmentioning
confidence: 92%
“…For example, Canas et al (2009) demonstrated an up-regulation of A 2A receptors in ageing in the hippocampus, where those receptors are present presynaptically (Canas et al 2009) while in the CB A 2A receptors are present postsynaptically (Conde et al 2006a). In contrast with this up-regulation of A 2A receptors, other authors have shown that adenosinergic activities were unaffected by ageing in the cerebellum and substantia nigra (for a review see Burnstock & Dale, 2015). Additionally, a reduction in P2X receptor expression in ageing mouse brain has been described as their role in glial synaptic current generation (Lalo et al 2011).…”
Section: Effects Of Ageing On Cb Cell Dynamicsmentioning
confidence: 99%
“…Thus, the frequent co-expression of P2X 3 with ORL1 receptors in TG neurons, found in the present study, provides a possibility for P2X 3 receptor modulation by N/OFQ at single-cell level through activation of the ORL1 receptor. However, previous evidence showed that P2X 3 receptors had developmental roles and that the expression of P2X3 in TG neurons decreases with postnatal development (31,32); therefore, the distribution of P2X 3 -positive neurons, as well as the co-localization with ORL1, may be significantly different for adult trigeminal neurons, and any interactions seen in neonatal neurons may not replicate what occurs in adult neurons.…”
Section: Discussionmentioning
confidence: 95%
“…It was shown that most extracellular Ado derives from extracellular adenosine 5′-triphosphate (eATP), [18], due to the action of the widely distributed ectonucleotidases NTPDase I (CD39), and NT5E (CD73) on eATP. Signals delivered by eATP and Ado are transduced by functional P1, P2Y and P2X receptor subtypes, respectively [19]. ATP can be generated by oxidative phosphorylation occurring exclusively inside the mitochondrion, occasionally released outside the cells due to death or lysis.…”
Section: Introductionmentioning
confidence: 99%